2018
DOI: 10.1002/jcsm.12354
|View full text |Cite|
|
Sign up to set email alerts
|

Protein imbalance in the development of skeletal muscle wasting in tumour‐bearing mice

Abstract: BackgroundCancer cachexia occurs in approximately 80% of cancer patients and is a key contributor to cancer‐related death. The mechanisms controlling development of tumour‐induced muscle wasting are not fully elucidated. Specifically, the progression and development of cancer cachexia are underexplored. Therefore, we examined skeletal muscle protein turnover throughout the development of cancer cachexia in tumour‐bearing mice.MethodsLewis lung carcinoma (LLC) was injected into the hind flank of C57BL6/J mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
143
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(155 citation statements)
references
References 76 publications
(136 reference statements)
10
143
1
1
Order By: Relevance
“…During the course of cancer therapy, body composition may change and influence outcomes of cancer patients . Body composition changes could be associated with systemic inflammation, treatment‐related toxicity, physical inactivity, malnutrition, cancer invasiveness, and cancer therapy . Therefore, evaluating the body composition at a single specific time point may not help in predicting survival.…”
Section: Introductionmentioning
confidence: 99%
“…During the course of cancer therapy, body composition may change and influence outcomes of cancer patients . Body composition changes could be associated with systemic inflammation, treatment‐related toxicity, physical inactivity, malnutrition, cancer invasiveness, and cancer therapy . Therefore, evaluating the body composition at a single specific time point may not help in predicting survival.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in body composition during cancer therapy have been associated with treatment‐related toxicity, physical inactivity, malnutrition, cancer invasiveness, and cancer therapy, which in turn could influence patient outcomes . Therefore, the prognostic value of body composition measurements in stage III EC needs to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Changes in body composition during cancer therapy have been associated with treatment-related toxicity, physical inactivity, malnutrition, cancer invasiveness, and cancer therapy, which in turn could influence patient outcomes. [18][19][20][21][22][23][24][25][26] Therefore, the prognostic value of body composition measurements in stage III EC needs to be evaluated. It has been shown that the cross-sectional areas of skeletal muscle and adipose tissue on a single computed tomography (CT) slice at the level of the third lumbar vertebra are strongly correlated with the total body skeletal muscle and adipose tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The circulating tumor cells (CTCs) in LACC may not be completely eradicated by CCRT [3][4][5][6]29]. Elevated CTCs levels are also associated with poor disease-free survival in LACC [29], implying that residual CTCs after CCRT might contribute to progressive muscle loss before resulting in gross detectable distant failures [30,31]. In the current study, we found that patients with muscle loss had a significantly shorter time to distant failure and worse DRFS.…”
Section: Discussionmentioning
confidence: 54%